Operations Research Proceedings 2017 Selected Papers of the Annual International Conference of the German Operations Research Society (GOR), Freie Universiät Berlin, Germany, September 6-8, 2017 (Operations Research Proceedings, GOR (Gesellschaft für Operations Research e.V.), 2018)
This book gathers a selection of peer-reviewed papers presented at the International Conference on Operations Research (OR 2017), which was held at Freie Universität Berlin, Germany on September 6-8, 2017. More than 800 scientists, practitioners and students from mathematics, computer science, business/economics and related fields attended the conference and presented more than 500 papers in parallel topic streams, as well as special award sessions. The main theme of the conference and its proceedings was "Decision Analytics for the Digital Economy.".